A R2p/R1p Ratiometric Procedure to Assess Matrix Metalloproteinase‐2 Activity by Magnetic Resonance Imaging1. Issue 14 (28th February 2013) - Catanzaro, Valeria; Gringeri, Concetta V.; Menchise, Valeria; Padovan, Sergio; Boffa, Cinzia; Dastrù, Walter; Chaabane, Linda; Digilio, Giuseppe; Aime, Silvio
<x xml:space="preserve">Abstract</x> Parametric MRI: A paramagnetic gadolinium‐loaded liposome for the MRI assessment of the activity of matrix metalloproteinase‐2 (MMP‐2) is described. The assessment relies on a procedure that involves the ratio R2p/R1p between the transverse and longitudinal paramagnetic contributions to the water proton relaxation rate. This method is independent of the total gadolinium concentration.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>